Information and communication technologies for economic and regional developments - Rahman, Hakikur (Hershey : Idea Group Pub., 2006)
This book includes evolution, planning, development, implementation and practical implications of diversified development practices around the world, focusing on socio-economic empowerment and regional developments through ICTs; it provides recommendations, success cases and failures of those practices that can be taken into consideration for future project preparation - Provided by publisher
Includes bibliographical references and index.
Keywords: Information technology -- Economic aspects; Technological innovations -- Economic aspects; Economic development; Regional planning